Ідентифікація нелінійних параметрів асинхронного двигуна у пусковому режимі з живленням від електромеханічного накопичувача енергії - Руденко, Микита Андрійович; Зачепа, Юрій Володимирович (Національний технічний університет "Хаківський політехнічний інститут", 2019)
В роботі розглянуто питання ідентифікації електромагнітних параметрів загальнопромислових асинхронних двигунів, що працюють здебільшого в повторно-короткочасних та короткочасних режимах роботи. Запропоновано спосіб ідентифікації електромагнітних параметрів асинхронних двигунів під час пуску на основі енергетичного методу. Розроблено схемне рішення реалізації запропонованого способу ідентифікації з живленням досліджуваного асинхронного двигуна від електромеханічного накопичувача енергії. Для підвищення точності ідентифікації запропонований підхід, що враховує ефект витіснення струму в роторі, у вигляді залежності активного опору ротора від струму.

The paper deals with the identification of electromagnetic parameters of general industrial induction motors operating mainly in intermittent and short-term operating modes. The paper proposes a method for identification of electromagnetic parameters of induction motors which based on the energy method when powered by electromechanical energy storagedevices. Developed schematic implementation of the proposed methodfor identification of parameters with formation of the required levels of energy effects when powering investigated induction motor from electromechanical en-ergy storage device. To improve the accuracy of identificationof electromagnetic parameters of induction motors during start-up, an approach is proposed that takes into account the effect of current displacement in the rotor, in form of dependence of rotor resistance on current. It has been experimentally proven that the proposed approach allows with sufficient accuracy to identify the electromagnetic parameters of induction motor. Studies installed expediency identification of EMP of IM with taking into account effect of current displacement when supplying by decaying signal of DC voltage on the stator winding and followed harmonic analysis of the current and voltage, determining an actual value of the rotor’s resistance.
Identification of nonlinear parameters of induction motor in the start-up powered supplied from electromechanical energy storage device
Keywords: енергетичний метод; миттєва потужність; ефект витиснення струму в роторі; energy method; instant power; current displacement effect in the rotor